Efektivitas Penggunaan Media Flipcard Mini Berorientasi Visual Storytelling terhadap Hasil Belajar Pendidikan Pancasila Siswa Madrasah Ibtidaiyah - Mila Khoirun Nisa; Rofi'ah, Siti (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to analyze the effect of using Flipcard Mini media based on visual storytelling on students’ learning outcomes in the Pancasila Education subject for fourth-grade students at MI Al As’ad Brambang Jombang. Flipcard Mini is designed to help students understand Pancasila values through two-sided illustrations that construct simple visual narratives. This research employed a quasi-experimental design using a one-group pretest–posttest model involving 30 students. Data were collected through learning outcome tests and analyzed using the Wilcoxon Signed Rank Test, indicated that the data were not normally distributed. The results show a significant increase between the pretest and posttest scores, demonstrating that Flipcard Mini effectively enhances students’ understanding of Pancasila concepts. These findings indicate that visual storytelling media can create more engaging, interactive, and meaningful learning experiences, making it a suitable alternative instructional medium for elementary school Pancasila Education.